MODEL EVALUASI PEMBELAJARAN AUD BERBASIS DARING DI RA NURUN NAMIRAH MEDAN MARELAN (STUDI KASUS SELAMA MASA PANDEMI COVID-19) - Syahruddin Damanik; Muhammad Zuhdi; Hazizah Hazizah; Herlina Herlina (STIT Al-Ittihadiyah Labuhanbatu Utara, 2020)
This study aims to analyze: (1) the variety of evaluation difficulties during Covid-19 learning, (2) alternative learning evaluation models during the Covid-19 pandemic, and (3) the obstacles faced in implementing various alternative learning evaluation alternatives. This research was conducted at RA Nurun Namirah Medan Marelan, using qualitative research methods based on descriptive studies. The data collection techniques used were observation, interview, and documentation study. The results of the study indicate that some of the difficulties are: (1) Difficulty in determining the form of learning evaluation. (2) It is difficult to map the indicators of learning achievement, (3) It is difficult to apply honesty values. So to overcome this difficulty teachers at RA Nurun Namirah innovated by designing and implementing alternative learning evaluation models in the midst of the Covid-19 pandemic, the alternative models were as follows: (1) portfolio-based learning evaluation, (2) oral-based evaluation, (3) Practice-based evaluation. However, it cannot be denied that in the application of the alternative evaluation model there are several obstacles faced, namely: (1) Lack of enthusiasm from parents and students, (2) Lack of parental understanding in the application of the evaluation model, (3) Lack of teacher and parent collaboration.